Late outcomes of endovascular aortic stent graft therapy in patients with chronic kidney disease. Issue 37 (11th September 2020) - Wu, Chung-Cheng; Chou, An-Hsun; Lin, Yu-Sheng; Wu, Victor Chien-Chia; Chang, Shang-Hung; Chu, Pao-Hsien; Cheng, Yu-Ting; Ko, Po-Jen; Liu, Kuo-Sheng; Chen, Shao-Wei
Abstract : Abstract: Endovascular aneurysm repair (EVAR) and thoracic endovascular aortic repair (TEVAR) are effective and minimally invasive treatment options for high-risk surgical candidates. Nevertheless, knowledge about the management of aortic stent graft therapy in chronic kidney disease (CKD) is scarce. This study aimed to examine outcomes after EVAR and TEVAR in patients with CKD. Utilizing data from the Taiwan National Health Insurance Research Database, we retrospectively assessed patients who underwent EVAR and TEVAR therapy between January 1, 2006, and December 31, 2013. Patients were divided into CKD and non-CKD groups. Outcomes were in-hospital mortality, all-cause mortality, readmission, heart failure, and major adverse cardiac and cerebrovascular events. There were 1019 patients in either group after matching. The CKD group had a higher in-hospital mortality rate than the non-CKD group (15.2% vs 8.3%, respectively; odds ratio, 1.92; 95% confidence interval [CI], 1.46–2.54). Patients with CKD had higher risks of all-cause mortality including in-hospital death (46.1% vs 33.1%; hazard ratio [HR], 1.61; 95% CI, 1.35–1.92), readmission rate (62.6% vs 55.0%; subdistribution HR [SHR], 1.61; 95% CI, 1.32–1.69), redo stent (7.8% vs 6.2%; SHR, 1.50; 95% CI, 1.09–2.07), and major adverse cardiac and cerebrovascular events (13.3% vs 8.8%; SHR, 1.50; 95% CI, 1.15–1.95). The subgroup analysis did not demonstrate a variation in mortality between the TEVAR and EVAR cohorts ( P for interaction = .725). The dialysis group had higher risks of all-cause mortality and readmission than the CKD without dialysis and non-CKD groups. Among EVAR/TEVAR recipients, CKD was independently associated with higher in-hospital mortality, postoperative complication, and all-cause mortality rates. Patients with end-stage renal disease on dialysis had worse outcomes than those in the CKD non-dialysis and non-CKD groups. Abstract : Supplemental Digital Content is available in the text